Pengembangan Media Audio Visual Berbasis Aplikasi Canva Pada Pembelajaran Tematik di Sekolah Dasar - Heri Maria Zulfiati; Pramudya Cahyandaru; Tansa Wahyu Agustina (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
The purpose of this study is to evaluate the validity and effectiveness of Canva application-based audio-visual learning media in the context of Thematic learning. This research uses the R&D method using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. However, in this study, only the Development stage is carried out because the goal is only limited to developing and producing learning media that are feasible to be implemented, based on assessments and suggestions from validators. The output of this research is a product in the form of learning media and articles that will be published in accredited national journals. TKT in this study is 1.